Analysis of the need for e-book adaptive physical education to physical education students at University of Bengkulu - Yahya Eko Nopiyanto; Cahyo Wibowo; Ibrahim Ibrahim (Universitas Sriwijaya, 2023)
The need for e-books in adaptive physical education courses needs to be done to meet the needs of physical education students at the University of Bengkulu. Analysis of the needs of e-books is a key factor in knowing the needs of students in attending adaptive physical education courses. This study aims to determine the level of need for adaptive physical education e-books for physical education students. This research is qualitative descriptive. Instruments and data collection techniques using observation, questionnaires, and interviews. A total of 1 lecturer supporting adaptive physical education courses, and 22 students selected purposively were involved to provide research data. Data analysis using data triangulation. The results of the analysis of the data stated that: 1) lecturers have limited time to develop an e-book, and 2) students need the e-book to support the lecture process. So it can be concluded that the need for adaptive PE e-books is in the very high category. Therefore, it is necessary to develop an e-book to meet the needs of physical education students in participating in adaptive physical education lectures at the Bengkulu University physical education study program.